Preface: 4th International Conference on Global Business and Management Science (GBMS 2024) - Turner, Abigail; Zhang, Hui (Transactions on Economics, Business and Management Research, 2024)
The 2024 4th International Conference on Global Business and Management Science (GBMS 2024) was held during July 13-14, 2024, in Vancouver, Canada. It is one of the conferences for presenting novel and fundamental advances in the fields of global business, economic systems, corporate governance, financial economics, management science, marketing research, and human resource.GBMS 2024 provides an excellent international platform for the academicians, researchers, and industrial experts from around the world to share their research findings with the global experts. The event is also an opportunity for PhD students in this area to moot their dissertation works to a global audience. The key intention of this seminar is to provide opportunity for the global participants to share their ideas and experience in person with their peers expected to join from different parts of the world. In addition, this gathering will help the delegates to establish research and business relations and linkage for future collaborations in their career path. We hope that the outcome of this conference will lead to significant contributions towards creation of new knowledge.The idea of the GBMS 2024 is for the scientists, scholars, engineers and students from the universities all around the world and the industry to present ongoing research activities, and hence to foster research relations between the universities and the industry. There is a real opportunity among a wide range of scientists, teachers, industry representatives, and students in various fields related, to exchange ideas, share knowledge and establish close cooperation.Regards,The Organizing Committees of GBMSVancouver, Canada